IMPLEMENTASI KEBIJAKAN PERIZINAN SISTEM ONLINE SINGLE SUBMISSION (Studi Pada DPMPPTSP Kabupaten Lampung Selatan) - Putra, Budi Utomo Jaya; Makhya, Syarief; Mukhlis, Maulana (Jurnal Analisis Sosial Politik, 2021)
Online Single Submission (OSS) is a form of application that aims to facilitate investment through the application of an electronically integrated business licensing system. However, in fact, there is a gap between the expected goals and the reality that occurs on the ground. This study aims to analyze the implementation of policies on licensing through the OSS system at the Investment Service and One Stop Integrated Licensing Service (DPMPPTSP) of South Lampung Regency using the theoretical approach of George C. Edwards III. This research uses descriptive research with a qualitative approach design. Based on the research results, it is known that the OSS System Licensing Policy Implementation at DPMPPTSP South Lampung Regency has not been successfully implemented optimally in accordance with the expected objectives, namely to provide convenience in licensing services. The factor that causes the OSS system licensing policy to be unsuccessful in being implemented optimally is the poor communication factor, namely the dimension of information transmission/delivery and the clarity of the information conveyed. Meanwhile, the resources, disposition and structure of the bureaucracy are generally quite good, although there are still things that need to be improved.